Social Values Perceptions of Fourth Grade Primary School Students - Hakan Cetin; Ozlem Kaf (European Scientific Journal, ESJ, 2017)
This study was conducted with the aim of determining the perceptions of social values of fourth grade primary school students. The research is a descriptive study based on survey model. The study sample group is composed of 451 fourth grade students studying in four different schools in Siirt city center selected via convenience sampling method. The Perception Scale for Social Values developed by Bakaç (2013) was used as data collection instrument. There are a total of 23 five-point likert-type items on The Perception Scale for Social Values, of which 19 items are designed to measure positive perceptions and 4 items are designed to measure negative perceptions. Cronbach-Alpha reliability coefficients of the scale are .88 for the first sub-scale, .72 for the second sub- scale and .86 for the total scale. Descriptive statistics, Mann-Whitney U-Test and Kruskal Wallis methods were used for data analysis. The findings of the study indicate that the social value perceptions of fourth grade students show no significant difference with regard to gender or education level of mother. Whereas it was concluded that the social value perceptions of fourth grade students show a significant difference with regard to place of residence and education level of father